Theoretical and experimental investigation of low-power AF-MPDT performance in the high mass flow rate low discharge current regime. (January 2019) - Kitaeva, Alena; Tang, Haibin; Wang, Baojun; Andreussi, Tommaso
Abstract: We performed a test campaign in order to fill the gaps in the experimental data and understanding of the performance of the Applied Field Magnetoplasmadynamic Thruster in low current, high mass flow rate regime. Thrust and discharge voltage were measured for two anode geometry configurations with different mass flow rate distribution, discharge current and external magnetic field strength. The general trends in thruster behavior using argon as propellant are analyzed in this paper and an approach for thruster optimization is investigated. We find an unexpectedly weak dependence of thrust efficiency on discharge current in low current, high mass flow rate regimes. Using a cylindrical anode configuration, we managed to achieve thrust efficiency of 21%, which is significantly higher than that reported in literature for AF-MPDTs operating in this regime. Highlights: Thruster operating with 1 kA 2  s/g should be a hybrid solution between arcjet and AF-MPDT. CYL had higher efficiency than C-D, due to a better propellant heating and ionization. Electro-Magnetic thrust becomes essential over 0.05 T applied field strength. IV characteristics is flat for all regimes and both thrusters. Cathode-based feeding strategy "C" shows better performance.